Therapeutic strategies of glioblastoma (GBM): The current advances in the molecular targets and bioactive small molecule compounds - Hui Liu; Weimin Qiu; Tianyu Sun; Lei Wang; Chenxi Du; Yanyu Hu; Wenyuan Liu; Feng Feng; Yao Chen; Haopeng Sun (Elsevier, 2022)
Glioblastoma (GBM) is the most common aggressive malignant tumor in brain neuroepithelial tumors and remains incurable. A variety of treatment options are currently being explored to improve patient survival, including small molecule inhibitors, viral therapies, cancer vaccines, and monoclonal antibodies. Among them, the unique advantages of small molecule inhibitors have made them a focus of attention in the drug discovery of glioblastoma. Currently, the most used chemotherapeutic agents are small molecule inhibitors that target key dysregulated signaling pathways in glioblastoma, including receptor tyrosine kinase, PI3K/AKT/mTOR pathway, DNA damage response, TP53 and cell cycle inhibitors. This review analyzes the therapeutic benefit and clinical development of novel small molecule inhibitors discovered as promising anti-glioblastoma agents by the related targets of these major pathways. Meanwhile, the recent advances in temozolomide resistance and drug combination are also reviewed. In the last part, due to the constant clinical failure of targeted therapies, this paper reviewed the research progress of other therapeutic methods for glioblastoma, to provide patients and readers with a more comprehensive understanding of the treatment landscape of glioblastoma.